Impact of Carbon Monoxide/Heme Oxygenase on Hydrogen Sulfide/Cystathionine‐γ‐lyase Pathway in the Pathogenesis of Allergic Rhinitis in Guinea Pigs. (12th January 2015) - Yu, Shaoqing; Yan, Zhiqiang; Che, Na; Zhang, Xiaolin; Ge, Rongming
Abstract : Objective: The discovery of carbon monoxide (CO) and hydrogen sulfide (H2 S) as pathogenic signaling molecules in airway‐related diseases has led to significant insights into the pathophysiologic mechanisms underlying the development of allergic rhinitis (AR). The potential crosstalk between CO and H2 S signaling pathways in AR has not been adequately investigated. This study was performed to elucidate the mechanistic relationship between CO and H2 S in AR. Study Design: Experimental prospective animal study. Setting: Animal laboratory of Tongji Hospital, Tongji University, Shanghai, China. Subjects and Methods: A well‐established model of AR was used whereby guinea pigs (N = 24) were randomly divided into 4 treatment groups (n = 6 for each group): The first group received ovalbumin only; the second group was administered exogenous hemin, a CO‐binding metalloporphyrin; the third group received zinc protoporphyrin, an inhibitor of heme oxygenase‐1. A control group was challenged using only saline. Symptoms of AR were recorded, and quantitation of plasma CO and H2 S levels was performed. Expression of heme oxygenase‐1 and H2 S‐generating enzyme cystathionine‐γ‐lyase (CSE) were measured from nasal mucosa. Results: Plasma CO and heme oxygenase‐1 expression levels of nasal mucosa were significantly increased in the AR group compared to controls, whereas H2 S concentrations were significantly decreased. Exogenous administration of CO exacerbated allergic symptoms, resulting in higher levels of both CO and heme oxygenase‐1 expression, and a further reduction in H2 S levels and CSE expression. Zinc protoporphyrin decreased CO concentrations and increased levels of both H2 S and CSE expression. Conclusions: Results indicated an inverse relationship between H2 S levels and CO in the pathogenesis of AR.